1987
DOI: 10.1021/bi00384a025
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NADH-ubiquinone reductase by N,N'-dicyclohexylcarbodiimide and correlation of this inhibition with the occurrence of energy-coupling site 1 in various organisms

Abstract: The NADH-ubiquinone reductase activity of the respiratory chains of several organisms was inhibited by the carboxyl-modifying reagent N,N'-dicyclohexylcarbodiimide (DCCD). This inhibition correlated with the presence of an energy-transducing site in this segment of the respiratory chain. Where the NADH-quinone reductase segment involved an energy-coupling site (e.g., in bovine heart and rat liver mitochondria, and in Paracoccus denitrificans, Escherichia coli, and Thermus thermophilus HB-8 membranes), DCCD act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 52 publications
4
48
0
Order By: Relevance
“…Once unlocked, this oxidation is inhibited by rotenone or DCCD. The inhibition by DCCD is consistent with a direct coupling between electron transfer and proton translocation as earlier suggested for the oxidation of NADH (Yagi 1987;Yagi and Hatefi 1988). Rotenone and piericidin A can each bind to two sites, one close to a site in the 49-kDa subunit, the site structurally equivalent to that of the Ni-Fe site in [NiFe]-hydrogenases (Darrouzet et al 1998;Prieur et al 2001), and the other on Table 2 Kinetics of the reactions of NADH and NADPH with bovine Complex I-The NAD(P)H→FMN data are from freeze-quench experiments.…”
Section: Kinetic Issues Reactions With Nad(p)hsupporting
confidence: 89%
See 1 more Smart Citation
“…Once unlocked, this oxidation is inhibited by rotenone or DCCD. The inhibition by DCCD is consistent with a direct coupling between electron transfer and proton translocation as earlier suggested for the oxidation of NADH (Yagi 1987;Yagi and Hatefi 1988). Rotenone and piericidin A can each bind to two sites, one close to a site in the 49-kDa subunit, the site structurally equivalent to that of the Ni-Fe site in [NiFe]-hydrogenases (Darrouzet et al 1998;Prieur et al 2001), and the other on Table 2 Kinetics of the reactions of NADH and NADPH with bovine Complex I-The NAD(P)H→FMN data are from freeze-quench experiments.…”
Section: Kinetic Issues Reactions With Nad(p)hsupporting
confidence: 89%
“…It has been reported that DCCD binds mainly to the ND1 subunit in Hatefi's Complex I (Yagi 1987;Yagi and Hatefi 1988). The labelling was not affected by the complete inhibition by rotenone, although the ND1 subunit can bind this inhibitor as well (Earley and Ragan 1984;Earley et al 1987).…”
Section: >200 Msmentioning
confidence: 88%
“…4). Subunit 1 has been postulated to be a transmembrane protein and a site of proton translocation and energy coupling (59,60). In addition, subunit 1 has been proposed as the site for quinone binding (23), although an isolated subcomplex of bovine complex I in which ND-1 was absent was able to couple NADH oxidation to quinone reduction (20).…”
Section: Resultsmentioning
confidence: 99%
“…The carboxyl group-modifying reagent DCCD specifically inhibits mitochondrial complex I and the related NDH-1 from bacteria (51). In bovine complex I, DCCD modifies the membrane-spanning ND1 subunit (NuoH homologue in NDH-1) and inhibits both electron transfer and proton transport (52).…”
Section: Vol 188 2006 Sodium Ion Binding To Complex I From K Pneummentioning
confidence: 99%